An improved digital integral algorithm to enhance the measurement accuracy of Rogowski coil-based electronic transformers - Li, Zhenhua; Xiang, Xin; Hu, Tinghe; Abu-Siada, Ahmed; Li, Zhenxing; Xu, Yanchun (International journal of electrical power & energy systems, 2020)
•An improved digital integral algorithm with frequency self-adaption ability is proposed, and experimental results reveal the improved performance of the Rogowski coil-based electronic transformer equipped with the proposed digital integral algorithm.•Errors in harmonic currents measurement (up to 50th order) can be significantly reduced to a level less than 0.01% at a sampling frequency of 12.8 kHz by employing the proposed algorithm.•Furthermore, the proposed algorithm has the ability to eliminate the impact of frequency fluctuation around the power frequency. In order to promote the practical application of the Rogowski coil-based electronic transformers, it is of great necessity to handle the issues associated with the measurement error and interference in the integral process of the electronic transformer. In this paper, an improved digital integral algorithm with frequency self-adaption ability that aimed at overcoming the above-mentioned issues is proposed. Based on the electronic transformer calibration and harmonic measurement requirements, two specific applications of the proposed integral algorithm are carried out to validate the practical feasibility of the proposed algorithm. Experimental results reveal the improved performance of the Rogowski coil-based electronic transformer equipped with the proposed digital integral algorithm. Errors in harmonic currents measurement (up to 50th order) can be significantly reduced to a level less than 0.01% at a sampling frequency of 12.8 kHz by employing the proposed algorithm. For calibrating electronic transformers, results show that the performance of the proposed algorithm is better than the conventional trapezoidal integral algorithm and Simpson algorithm. Furthermore, the proposed algorithm has the ability to eliminate the impact of frequency fluctuation around the power frequency.